Hypoglycemic and anti-inflammatory effects of seabuckthorn seed protein in diabetic ICR mice. Issue 3 (26th February 2016) - Yuan, Huaibo; Zhu, Xiping; Wang, Wenjuan; Meng, Lina; Chen, Deyi; Zhang, Cuan
Abstract : In this paper, we have investigated the hypoglycemic and anti-inflammatory effects of seabuckthorn seed protein (SSP) on streptozocin (STZ)-induced diabetic IRC mice. Abstract : In this paper, we have investigated the hypoglycemic and anti-inflammatory effects of seabuckthorn seed protein (SSP) on streptozocin (STZ)-induced diabetic IRC mice. The effects of SSP on the body weight (BW), fasting blood glucose (FBG) levels, serum lipids, inflammatory factors and insulin (SIN) levels of normal and diabetic mice have been investigated. SSP has been shown to reduce insulin resistance (IR) and control the effects of C-reactive protein (CRP), interleukin-6 (IL-6), tumor necrosis factor-α (TNF-α) and nuclear factor-κ-gene binding (NF-κB). In addition, this paper further validates the hypoglycemic and anti-inflammatory effects of seabuckthorn procyanidins (SPR) and seabuckthorn polysaccharides (SPO) in diabetic mice and the experimental results were consistent with previous studies. Moreover, results from animal experiments showed that SSP has a significant hypoglycemic and anti-inflammatory effect as evidenced by the lower BW, FBG levels, SIN and lipid contents of diabetic mice treated with SSP compared to the diabetic control mice.